Contract in context - Austen-Baker, Richard; Zhou, Qi (Abingdon, Oxon : Routledge, 2015)
'Contract in Context provides an easy to read, in depth analysis of the purpose and role of contract law and the theories that surround it. It looks at the historical development of contract law as well as providing detailed analysis of some of the leading theoretical explanations and how they are applied on an international level. The book's accessibility is enhanced by text boxes defining key concepts and terms and by bullet-point lists and descriptions further enlivened by biographical notes for leading figures and scholars. This ensures that students are able to gain firm grasp and clear understanding of the narratives and theories explained in the book. Contract in Context is unique in that it is not limited to one jurisdiction, making it ideal for students around the globe wishing to develop or expand their knowledge of contract law'--
What is Contract for? and What is Contract Law for? -- The Historical Context of Contract -- The Ideological Context of Contract -- Classical & Neo-Classical Contract -- The Relational Context of Contract -- The Economic Theories of Contract Law : Part I -- The Economic Theories of Contract Law : Part II -- The International Context of Contract.
Keywords: Contracts